Mapping Japanese linguistics research in Indonesia: Trends, themes, and major contributors - Renold, Renold; Taqdir, Taqdir; Lantang, Ayu Gardenia; Muhammad Faiz Alghifari; Ery, Anda Prasetyo (Universitas Dian Nuswantoro, 2025)
This study aims to map the development of Japanese linguistics research in Indonesia through bibliometric analysis, focusing on trends, key themes, and major contributors in the field. Data were retrieved using the Publish or Perish software with Google Scholar as the primary source, covering the period from 2000 to 2024. Analytical tools such as VOS viewer and Tableau were utilized to examine annual publication trends, keyword co-occurrences, and author collaboration networks. The findings reveal a significant growth in publications post-2010, dominated by applied linguistics themes such as language teaching, public language use, and sociolinguistics, while theoretical studies, including sentence structure and semantic analysis, provide critical foundational insights. Key contributors were identified based on their productivity and citation metrics, highlighting patterns of inter-institutional collaboration. This study provides a comprehensive overview of Japanese linguistics research in Indonesia, bridging theoretical and practical perspectives. The findings underscore the importance of strengthening research collaboration and integrating applied and theoretical studies to advance Japanese language education and cross-cultural understanding in Indonesia Keywords: applied linguistics, bibliometric analysis, Indonesia, Japanese linguistics, Publish or Perish